Review article: Implicit bias towards Aboriginal and Torres Strait Islander patients within Australian emergency departments. (28th November 2020) - Quigley, Alyssa; Hutton, Jennie; Phillips, Georgina; Dreise, Darlene; Mason, Toni; Garvey, Gail; Paradies, Yin
Abstract: Aboriginal and Torres Strait Islander peoples continue to suffer adverse experiences in healthcare, with inequitable care prevalent in emergency settings. Individual, institutional and systemic factors play a significant part in these persisting healthcare disparities, with biases remaining entrenched in healthcare institutions. This includes implicit racial bias which can result in stereotyping of racial minorities and premature diagnostic closure. Furthermore, it may contribute to distrust of medical professionals resulting in higher rates of leave events and hinder racial minorities from seeking care or following treatment recommendations. The aim of this review is to analyse the effect of implicit bias on patient outcomes in the ED in international literature and explore how these studies correlate to an Australian context. Abstract : Implicit racial bias may result in stereotyping of racial minorities and premature diagnostic closure. Furthermore, it may contribute to distrust of medical professionals resulting in higher rates of leave events and hinder racial minorities from seeking care or following treatment recommendations. The aim of this review is to analyse the effect of implicit bias on patient outcomes in the ED in international literature and explore how these studies correlate to an Australian context.